Change in total lesion PSMA (TLP) during [177Lu]Lu-PSMA-617 radioligand therapy predicts overall survival in patients with mCRPC: monocentric evaluation of a prospective registry. - Burgard, Caroline; Hein, Connor; Blickle, Arne; Bartholomä, Mark; Maus, Stephan; Petto, Sven; Schaefer-Schuler, Andrea; Ezziddin, Samer; Rosar, Florian (European Journal of Nuclear Medicine & Molecular Imaging, 2024)
Purpose: This study investigates imaging response of [177Lu]Lu-PSMA-617 radioligand therapy (RLT) based on the whole-body parameter total lesion PSMA (TLP), derived by PSMA-PET/CT and reflecting the total tumor burden, in patients with metastatic castration-resistant prostate cancer (mCRPC) enrolled in a prospective registry (NCT 04833517). Methods: A total of n = 102 mCRPC patients received a [68Ga]Ga-PSMA-11 PET/CT at baseline and after two cycles of PSMA-RLT, in which TLP was measured by using a semi-automated tumor segmentation. TLP was defined as the summed products of volume and uptake (∑ Volume × SUVmean) of all tumor lesions. The Kaplan-Meier method was used to determine the most appropriate ∆TLP thresholds for classification into partial remission (PR), stable disease (SD), and progressive disease (PD) regarding overall survival (OS). Furthermore, we analyzed criteria that are also frequently used in established response frameworks, such as the occurrence of new metastases as independent criterion (I) or in combination with change in tumor burden (II), and the change in PSA serum value (III). Results: For the ∆TLP thresholds −30%/+30% (and also for higher thresholds, −40%/+40% or −50%/+50%), significant differences between all three response categories became apparent (PR/PD: p = 0.001; PR/SD: p = 0.001; SD/PD: p = 0.018). Including the development of new metastases as independent criterion of PD, there was no significant difference in OS between SD and PD (p = 0.455), neither when applied in combination with TLP (p = 0.191). Similarly, significant differentiation between SD and PD was not achieved by PSA serum value (p = 0.973). Conclusion: In the largest monocentric study to date, TLP is shown to be a qualified prognostic biomarker, applying ∆TLP thresholds of −30%/+30%. It significantly differentiated between PR, SD, and PD, whereas other response criteria did not differentiate SD vs. PD. Using TLP, the development of new metastases is not a required information for predicting OS.